Comparisons between education offerings for youth and adults with a focus on youth: profiles and spaces - Ribeiro, Eliane; Souza, Luiz Carlos; de Freitas, Maria Virgínia (Education Policy Analysis Archives, 2014)
This paper fits in debates on public policies for young people education in Brazil. In this context, performs comparisons between the offer of the Programa Nacional de Inclusão de Jovens – ProJovem Urbano (PJU) and the Education of young people and Adults (EJA). Our goal is to find evidences of PJU’s possible social effects over educational provision for young people, compared to the conditions offered by the EJA to its young audience. In the analysis, were developed basic descriptive statistics procedures, comparing profiles of students, teachers and schools, using data from the monitoring system of the PJU and also those from Censo Escolar – INEP database. Comparisons explain similarities and differences between the two scenarios. Statistically, the comparisons show that in some of the aspects analyzed PJU's offer is better than the EJA. On the other hand, also show ways in which the EJA offers better conditions than the PJU. These differences influence qualitatively the educational provision for young people and point to the need of a deeper approach to the understanding of its causes, as well as possible strategies for its treatment.